The role of job aids in supporting task sharing family planning services to community pharmacists and patent proprietary medicine vendors in Kaduna and Lagos, Nigeria - Sikiru Baruwa; Elizabeth Tobey; Emeka Okafor; Kayode Afolabi; Toyin O. Akomolafe; Innocent Ubuane; Jennifer Anyanti; Aparna Jain (BMC, 2022)
Abstract Background CPs and PPMVs are an important source of modern contraceptives in Nigeria, yet many lack the requisite knowledge and skills to capably provide these services. This skills gap might be addressed through targeted family planning (FP) training. This study measures family planning knowledge retention of CPs and PPMVs after receiving training in FP counseling and services in Kaduna and Lagos States, in Nigeria. Methods In a quasi-experimental longitudinal design without a comparison group, 559 CPs and PPMVs who were enrolled in the IntegratE project between January and December 2019, completed a self-administered questionnaire to assess their knowledge related to the provision of FP counseling, and injectable and implant contraceptive services at three points in time: 1) before the training; 2) immediately after the training; and 3) 9-months after the training in Kaduna and Lagos states, Nigeria. Adjusted multivariate logistic regression analysis was used to assess the effect of provider characteristics and receipt of job aids on FP knowledge retention 9 months after the training. 95% confidence intervals and p-values were used to assess statistical significance. Results Majority of study participants were females (60.3%) and between 30 and 49 years old (63.4%). The study revealed the importance of jobs aids as influence on knowledge retention. CPs and PPMVs who reported having the Balanced Counseling Strategy plus (BCS+) counseling cards, were more likely to retain knowledge (AOR: 2.92; 95% CI: 1.01-8.40, p-value = 0.05) at 9 months follow-up. Similarly, in terms of knowledge of injectable contraceptives, CPs and Tier 2 PPMVs who reported receiving the Medical Eligibility Criteria (MEC) Wheel were 2.1 times more likely to retain knowledge of injectable contraceptives 9-months later on (95% CI: 1.14-3.99, p-value = 0.02). Conclusion Community Pharmacists and Proprietary Medicine Vendors had good retention of family planning knowledge, especially when combined with job aids. Training and providing them with job aids on FP will therefore support task shifting and task sharing on family planning services provision in Nigeria.